Quinua como promotor de valores sociales en las comunidades rurales de Boyacá (2016)
This research develops an approach previously used for the identification of relevant values in agricultural associative activities. This research is done from the social scienceperspective and is based on the analysis of testimonies of those involved in Quinoa farming in the department of Boyaca Colombia, from which we draw expressions that testify of the importance and prevalence of semiotic referents and axiological signifiedspresent in the social process that occurs when promoting this crop. Naturally it has a qualitative methodological approach and seeks to give guidelines to learn the causes of the poor development of this activity and to adopt institutional and community policies for his future improvement.